Simultaneous Determination of Methanol and Ethanol Residues in Biodiesel by a Simple Headspace Single-Drop Microextraction and Gas Chromatography with Flame Ionization Detection - Boonmalai, Apichart; Jakmunee, Jaroon; Kritsunankul, Orawan (Naresuan University Journal: Science and Technology (NUJST), 2016)
A simple sample preparation by headspace single-drop microextraction (HS-SDME) and gas chromatography-flame ionization detection (GC-FID) methods were developed for the simultaneous determination of methanol and ethanol residues in biodiesel. The analytes were manually extracted from a mixed standard or sample solutions into a suspended microdrop of ultrapure water containing isobutanol as an internal standard. After extraction, the extracted analytes were injected into GC-FID and separated under the high polarity capillary column (30 m x 0.25 mm i.d. x 0.25 µm) and oven temperature program. Optimization of parameters for the GC-FID and the extraction procedure was carried out, such as oven temperature programs, volumes of microdrop, incubation and extraction times, and temperatures of incubation and extraction. Under the optimum conditions, the order of elution was methanol, ethanol and isobutanol, respectively, with the analysis time of 16.7 min per chromatogram. Linear calibration graphs were in the range of 1.0x10 -4 - 1.0x10 -2 %v/v for both analytes with the limit of detections of 2.4x10 -5 and 7.5x10 -6 %v/v for methanol and ethanol, respectively. A sample throughput of about 2.5 h -1 was achieved. The proposed methods were successfully applied to real biodiesel samples. Acceptable recoveries and relative standard deviations were achieved, which were in the ranges of 94±4 - 106±4 % and 1.7 - 8.3 %, respectively, by spiking all samples with mixed standard solution of methanol and ethanol. The developed method had advantages of simple extraction and operation, no organic solvent used for extraction, low consumption of extraction solvent and material, inexpensive of extraction techniques, and acceptable accuracy and precision. Keywords : Methanol, Ethanol, Biodiesel, Single-drop microextraction, Gas chromatography
Keywords: Methanol, Ethanol, Biodiesel, Single-drop microextraction, Gas chromatography